2015
DOI: 10.1177/1077801215584068
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Consequences Associated With Positive and Negative Responses to Disclosure of Sexual Assault Among College Women

Abstract: A prospective design was utilized to explore the impact of social reactions to sexual assault disclosure among college women who experienced sexual victimization over a 4-month academic quarter. Women completed baseline, 4- and 7-month assessments of symptomatology, beliefs about why sexual assault occurs, victimization, and social reactions to sexual assault disclosure. Accounting for symptomatology or beliefs reported prior to the assault, positive social reactions were not associated with victims’ subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 69 publications
6
80
0
Order By: Relevance
“…One study found only 70% of colleges had information on whom to contact after a sexual assault is reported (Sabina & Ho, 2014). In addition, even when there is a response, some students have a negative experience after reporting an assault which can cause a secondary victimization and negatively impact the recovery process (Orchowski, & Gidycz 2015). These system issues create a culture where students don't want to report a sexual assault.…”
Section: Sourcesmentioning
confidence: 99%
“…One study found only 70% of colleges had information on whom to contact after a sexual assault is reported (Sabina & Ho, 2014). In addition, even when there is a response, some students have a negative experience after reporting an assault which can cause a secondary victimization and negatively impact the recovery process (Orchowski, & Gidycz 2015). These system issues create a culture where students don't want to report a sexual assault.…”
Section: Sourcesmentioning
confidence: 99%
“…Help-providers' responses to disclosures can affect survivors' well-being after an assault. Survivors who receive positive, supportive reactions following a disclosure report better mental health (e.g., Campbell, 2008;Orchowski, Untied, & Gidycz, 2013;Ullman, 1999), while negative, unsupportive reactions exacerbate survivors' psychological distress (e.g., Orchowski & Gidycz, 2015;Orchowski et al, 2013;Ullman, & Relyea, 2016). Policies that require employees to report a student's identifying information to the university after a sexual assault disclosure even if the student does not want to report may be experienced negatively by employees and students (Holland et al, 2018).…”
Section: Ra Roles Under Federal and Institutional Policymentioning
confidence: 99%
“…Academic psychiatrists should assist in developing campuswide training programs aimed at educating campus leaders, such as college officials, administrators, professors, counselors, and resident advisors, in how to appropriately and effectively respond to incidents of sexual violence in ways that support survivors [25]. Given the low rates by which students report sexual assault to official campus agencies [5] and the higher likelihood that they will discuss the incident with a peer [25], supervised peer counseling services should be established to provide safe spaces where students can discuss their experience in confidence and learn about further resources available to them on campus.…”
Section: Additional Training For Campus Leadersmentioning
confidence: 99%
“…Given the low rates by which students report sexual assault to official campus agencies [5] and the higher likelihood that they will discuss the incident with a peer [25], supervised peer counseling services should be established to provide safe spaces where students can discuss their experience in confidence and learn about further resources available to them on campus. Moreover, medical and mental health professionals working on college campuses should be informed about the situational factors that may contribute to risk and should be trained to sensitively, validly, and routinely screen for a history of sexual assault.…”
Section: Additional Training For Campus Leadersmentioning
confidence: 99%